KETERLIBATAN WANITA DALAM BERPOLITIK - Sukarno, Bedjo (Transformasi, 2011)
Abstrak   Women's political democracy has not been as expected, women's political democracy implies only on respect of  sovereignty inherent in  every human.   Involvement of women in the political field has long been a concern of society, because it remains political women to fight for women's rights. Key words: women's involvement in politics, women's political rights